The Influence of Sense of Community on the Perceived Value of Physical Activity: A Cross-Context Analysis. (26th May 2016) - Pickett, Andrew C.; Goldsmith, Andrew; Damon, Zack; Walker, Matthew
ABSTRACT: As the physical activity marketplace becomes increasingly diversified, strategies for recruiting and maintaining participants have become especially salient. Accordingly, the current study examined the use of a commonly reported outcome of fitness participation, sense of community (SOC), as an antecedent in generating both value and the perception of progress for participants. Three fitness contexts, CrossFit, traditional group fitness activities, and individual gym goers, were chosen based on varying levels of explicit commitment to community building. SOC was first measured in three contexts to explore differences among settings. After establishing differences between groups, multiple regression analysis was employed to understand the ways in which SOC affected dimensions of value. Results indicated that an explicit commitment to community building was positively associated with higher value of the fitness product and perceptions of individual progress. Strategy and benefits for encouraging the development of SOC in a fitness context are discussed.